The impact of atmospheric moisture transport on winter Arctic warming: Radiation versus latent heat release. (23rd February 2021) - Hao, Mingju; Lin, Yanluan; Luo, Yong; Nath, Reshmita; Zhao, Zongci
Abstract: Atmospheric moisture transport (AMT) contributes significantly to the recent accelerated Arctic warming. However, the impact of AMT has not been well quantified, not to mention the relative contribution of its impact on microphysical latent heating (LAH) and longwave radiative heating (LWH). A series of Polar‐WRF model experiments with different magnitudes of AMT are conducted to study the response of winter Arctic temperature to AMT variations. Results show that atmospheric precipitable water is very sensitive to AMT variations and thus can define the changes in surface air temperature by altering surface downward longwave radiation. Additionally, because evaporation and sublimation tend to balance the AMT‐induced moisture changes near the surface, LWH in the lower troposphere is determined by downward longwave radiation and thus can be the dominant factor for temperature variations. However, temperature in the mid‐ and upper troposphere is primarily determined by changes in LAH, because the content of ice‐phase cloud aloft is significantly affected by AMT. In addition, the changes in LWH in the mid‐ and upper troposphere are governed by upward longwave radiation, thus offsetting some of the temperature variations. These findings have implications for the attribution of Arctic current warming and the prediction of its future temperature change. Abstract : Changes in atmospheric moisture transport (AMT) will induce changes in latent heating (LAH) in the atmosphere that are slightly larger than changes in longwave radiative heating (LWH). During strong AMT episodes, LAH is the dominant factor of winter Arctic temperature rises in the mid‐ and high‐troposphere. In addition, LWH significantly contributes to the increase in temperature near the surface, but balances some of the increase in temperature in the mid‐ and upper troposphere.